A Feasibility Study of a Telehealth Intervention on Health Care Service Utilization among Transgender Women of Color in Washington, DC - Magnus, Manya; Edwards, Elizabeth; Dright, Aurnell; Gilliam, Leandrea; Brown, Angela; Levy, Matthew; Sikka, Neal; Siegel, Marc; Criss, Vittoria; Watson, Christopher Chauncey; Machtinger, Edward; Kuo, Irene (ACI Open, 2018)
Background Transgender women of color (TWC) are a medically underserved population who often experience substantial barriers to care. TWC experience high rates of stigma, violence, and entrenched barriers to receiving routine or specialty health services. Novel ways to improve access for TWC are urgently needed. Telehealth is one way to support TWC in overcoming barriers, yet this approach has been largely unexamined. The purpose of this study was to develop a TWC-specific telehealth intervention to increase access to primary and specialty care and then pilot test this intervention in a sample of TWC with at least one structural barrier to care.Methods Eligible participants were 18 years or older, identified as male sex at birth with a current gender identity of either female or transgender, a member of a racial/ethnic minority, and had experienced at least one study-defined structural barrier to primary or specialty care in the past 6 months. Following a 3-month preintervention phase, participants began a 3-month telehealth intervention which provided secure, remote access to trained, culturally appropriate, peer health consultants (PHCs) via video chat, e-mail, text, or phone. Health care utilization was assessed monthly via computer-assisted self-interview. Outcomes of intention to seek care in the next month and receipt of care in the past month were modeled using generalized estimating equations (GEE).Results Twenty-five eligible participants were enrolled in the study; a majority were black (96%), older than 25 years (69%), living with human immunodeficiency virus (HIV) (52%), and reported depressive symptomatology (67%). Of the 16 who had at least one pre- and one intervention data collection point, 13 downloaded the mobile video chat application and 7 participated in a qualitative exit interview. The intervention was associated with significantly (p < 0.05) increased odds of intention to seek transgender-specific care (adjusted odds ratio, aOR: 1.76 [95% confidence interval, CI: 1.001–3.08]); participants with depression defined by an elevated Center for Epidemiologic Studies 8-item depression scale (CES-D-8) score were significantly more likely to have intention to seek specialty care (aOR: 10.53 [95% CI: 1.42–77.97]), HIV-specific care (aOR: 2.56 [95% CI: 1.27–5.17]), and mental health care (aOR: 2.56 [95% CI: 1.27–5.17]) during the intervention period. Participants with elevated CES-D-8 scores had significantly greater odds of having sought HIV-specific care (aOR: 2.31 [95% CI: 1.31–4.06]) during the intervention period relative to those with lower scores.Conclusion These pilot data suggest that telehealth with remote access to PHCs who can provide immediate, culturally competent, nonclinical, education, and referral guidance may be effective in overcoming multiple barriers and improving care utilization outcomes for TWC. Telehealth may be an innovative, low-cost solution to improve health outcomes for populations with multiple barriers to health care services.
Keywords: telehealth; telemedicine; transgender women; HIV